Social Relations On Multicultural Society In The Context Of Social Change: Perspective Indonesia - Tobroni, H. (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2013)
Indonesia is one of the world mosaics. Vast archipelagic territory from Sabang to Merauke, there are hundreds of ethnics and languages and religions, making Indonesia one of the world's wonders. Develop appropriate patterns of social relations in a multi-cultural society such as this to be an important issue that horizontal conflicts and separatism can be avoided. Social change and social transformation in the political system from the bureaucratic system of the New Order authoritarian to democratic reform era in the setting- liberal globalization has implications for horizontal conflict, mass rioting and even separatism in various areas. Religious differences also play a role in increasing the scale of the conflict. The solution is not enough just through security approach and structural approach, but also takes a cultural approach and other approaches are more humane. develop the mind set of multiculturalism, tolerance and inter-religious cooperation and humanitarian projects and humanizing become more effective and more eternal in creating social resilience in a multi-cultural society in Indonesia.